Development of Physics Ethnoscience-Based Teaching Materials to Enhance Student’s Analytical Thinking Skills - Kariani, Kariani; Sukroyanti, Baiq Azmi; Habiburrahman, Lalu (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
This research aimed to develop physics teaching materials based on ethnoscience by integrating local culture wisdom to enhance high school students’ analytical thinking skills. The development model used was the 4D model: Define, Design, Develop, and Disseminate. The teaching materials were designed to meet students' needs and characteristics. The novelty of this research lies in the development of physics teaching materials based on the local ethnoscience of Bau Nyale, systematically designed in accordance with the Merdeka Curriculum to enhance students’ analytical thinking skills, thereby fostering contextual, applicable, and culturally responsive physics learning relevant to the demands of the 21st century. Validation results from two experts in content and media indicated that the materials were feasible, with feasibility scores of 75% (valid) and 83.3% (very valid), respectively. Suggestions for improvement were provided regarding examples of ethnoscience and layout design. Practicality test showed a very positive response from the teacher (85%) and a positive response from students (84.8%), indicating that the materials are user-friendly and support meaningful learning. In terms of effectiveness, the teaching materials significantly improved students’ analytical thinking skills (p < 0.001), with a high average N-Gain score of 0.764. The integration of local cultural context within the materials made physics concepts easier to understand, more contextual, and relevant to daily life, but also contributed to science education in general by fostering culturally responsive learning, strengthening students’ ability to connect culture with physics concepts, enhancing appreciation of local wisdom, and providing a reference for the development of ethnoscience-based science education in schools and higher education